Development of recipes for combined products with functional properties - O. A. Ogneva; N. S. Bezverkhaya (Новые технологии)
Currently, products with functional properties are becoming more and more important, therefore, it is relevant to expand the range of these products and increase their production. Taking into account the relevance of these products, we decided to develop new recipe compositions for functional food products containing the following main ingredients: fruit and vegetable raw materials, pectin, SMP (skim milk powder), whey, sourdough. In order to develop new recipes, the following tasks have been set: to study the chemical composition and physical and chemical properties of all recipe components; to determine the possibility of an increase in the prebiotic properties of the used vegetable and fruit raw materials; to investigate experimentally the possibility of simultaneous use of probiotic micro flora and fruit and vegetable raw materials treated with an enzyme preparation; to develop recipe compositions of fruit and vegetable products with functional properties; to analyze the functional orientation of the developed products. Vegetable and fruit raw materials in the form of puree and juices, milk whey obtained in the production of cottage cheese, pectin (liquid and dry), probiotic starter cultures in the form of concentrates of lactic acid and bifidobacteria, Pectinex Ultra SP-L pectolytic enzyme have been selected as the objects of the research. As a result of the research, we have developed new recipes for functional drinks and desserts, as well as analyzed their functional orientation. In accordance with the normative and technical documentation for functional food products the developed products can be classified as functional ones in terms of the content of the following functional sources: pectin, organic acids, minerals, and vitamins.